Implementasi Pendidikan Karakter di Pusat Kegiatan Belajar Masyarakat Homeschooling Primagama Semarang - Azahra, Luthvia Rizkiyanti; Ilyas, Ilyas (Journal of Nonformal Education and Community Empowerment, 2019)
The purpose of this study describes the process and constraints and more value in the implementation of character education. This research method using a qualitative approach with a descriptive method, data collection technique is done by interview, observation, and documentation. The data validity technique uses source triangulation and method triangulation. Data analysis techniques use data collection, data reduction, data presentation, and conclusions. The results of the research show that there are three stages of the implementation process, which are adjusted to the needs, the implementation of the integrated implementation of subjects and extracurricular self-development activities and the evaluation is done when the learning takes place and the end of learning. The inhibiting factors include the absence of written planning in extracurricular, changing psychological conditions and non-reuse of citizens' behavior forms. Supporting factors include parental support and outside cooperation, its value is the change of behavior to be better.